Penerapan Hukum Perikatan dan Sanksi Hukum terhadap Ayah yang Melalaikan Kewajiban Nafkah Anak Pasca Perceraian (Studi di Pengadilan Agama) - Arvhico Nasution; Reka Acintya Saditri; Zaqia Salsabillah. (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
This article discusses the application of the law of obligations and the effectiveness of legal sanctions against fathers who neglect their child support obligations after divorce, based on practice in Religious Courts. The obligation to provide child support is a legal obligation that remains in effect even after the marriage has ended. However, in practice, many fathers still fail to comply with child support decisions, resulting in serious impacts on the fulfillment of children's rights. This study uses a normative and empirical juridical approach to analyze the legal basis, forms of sanctions, and enforcement mechanisms. The results show that although Religious Courts have a strong legal basis for determining child support obligations, their implementation still faces obstacles, such as fathers' non-compliance, minimal oversight, and limited effective enforcement mechanisms. This study emphasizes the importance of protecting children's rights as a top priority in every post-divorce legal process.